Annual report 1996 of the CGIAR system-wide genetic resources programme - International Plant Genetic Resources Institute; CGIAR Systemwide Genetic Resources Programme (1997)
SGRP publishes every year a report providing a detailed overview of its activities. This report provides information on activities carried out in 1996.